Erratum: Publisher Correction: Rotating robots move collectively and self-organize (Nature communications (2018) 9 1 (931)) - Scholz, Christian; Engel, Michael; Pöschel, Thorsten (Nature Communications, 2018)
The original version of this Article contained an error in Fig. 5. In Fig. 5e, the scale on the y-axis originally incorrectly went from '0' to '1.10-4'. The correct scale goes from '0' to '0.4'. In Fig 5f, the x-axis labels were incorrectly shifted to the right. This has been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2021-12-22